Physical and psychological aspects of Brazilian sitting volleyball players, - Ahmadi, S. (2019)
Start point of the Sitting volleyball (SV) was in the Netherlands in 1956 and also approved as an official Paralympic game in 1980. In Brazil, SV is a new sport and it was launched at the end of 2002. Nowadays, male's and female's Brazilian SV teams in World ParaVolley Ranking are on the second and third place, respectively. SV is a big simplicity that shows a real example of adaptation and implementation of a major team sports. This work is structured on the basis of three-chapter format, as well as introduction and conclusion sections. In the first chapter, "Physical performance aspects", we presented comparisons among the agility, endurance, power, speed, and strength factors of male and female Brazilian elite SV players. There were statistically significant higher values for males in agility, speed, endurance, and power factors than female players, but there was no significant difference between players in handgrip performance (strength). In addition, according to isokinetic dynamometer test, the male and female SV players had an asymmetrical rotational strength in their shoulder, preference for the dominant side in both groups. In the second chapter, "Anthropometry and body composition aspects", we described the body composition of male and female highlytrained Brazilian SV players and also compared the values obtained of this players by Skinfolds (SF) and Air-displacement plethysmography (ADP) methods. There were no significant differences between the mean values of players which measured by ADP and SF for body fat percentage (BF%) and body density (BD). The analysis of BF% and BD for all players comparing ADP to SF resulted in no significant systematic bias. Also a high degree of reliability was found between ADP and SF measures of BF% and BD. There were statistically significant positive correlations between BF% and BD in all values for both methods. In the third chapter, "Psychological aspects", we analysed the quality of life (QOL), lifestyle, and mood aspects of male and female elite Brazilian SV players. The results of this study demonstrated there were not significant differences in the psychological aspects between the male and female players. These chapters provided an overview of the elite Brazilian SV players in physical, and psychological aspects, in which in all aspects gender differences of this population were considered. In clinical implication perspective, the present research can be seen as a first step in establishing a reference base concerning physical and psychological aspects in this specific para-athlete population. Also, this reference base could help Paralympic coaches, physiotherapists and Para-sports physicians in the evaluation of SV players.